A new channel and QoS-aware scheduling algorithm for real-time and non-real-time traffic in 5G heterogeneous networks - Queiroz, Gabriel Andrade (2024)
5G mobile communication systems present growing demands aimed at Quality of Service (QoS) requirements combined with the high densification of users in a heterogeneous network infrastructure (HetNet). Thus, 5G networks are expected to accommodate various applications and services. Therefore, it is necessary to develop scheduling methods that can benefit both real-time (RT) and non-real-time (NRT) services. In this sense, we propose two new scheduling algorithms, the Weighted QoS Aware Scheduler (WQAS) and the Channel and QoS Aware Scheduler (CQAS), in a HetNet scenario characterized by the diversity of traffic models: full buffer (IoT), HTTP, vehicular, VoIP, gaming, and video. System-level simulations are carried out to analyze the performance of WQAS and CQAS compared to the Round Robin (RR), best Channel Quality Indicator (CQI), and QoS Aware Scheduler (QAS) algorithms, considering the variation in the number of users as a way of stress testing the network. The results indicate that WQAS and CQAS show similar results for RT applications, with WQAS standing out for reliability. Furthermore, CQAS shows significant overall throughput gains except for HTTP when compared with QAS and WQAS. Both WQAS and CQAS perform well in adapting to the delay constraints related to the QoS requirements of each 5G RT application, in addition to good reliability performance. Finally, CQAS achieved the results described above for RT applications while generating the lowest impact on NRT applications, demonstrating the importance of a Channel and QoS-aware algorithm.